2015
DOI: 10.21071/az.v64i247.400
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de regressão para predição do peso da raça Canindé através de medidas morfométricas

Abstract: O presente trabalho teve como objetivo utilizar equações de predição para estimar o peso vivo de caprinos da raça Canindé mediante medidas morfométricas de natureza quantitativa. Foram avaliadas 347 fêmeas adultas da raça Canindé, provenientes de diferentes estados na região Nordeste do Brasil. Os animais foram pesados e, após as pesagens, com o auxilio de uma fita métrica foram tomadas medidas de altura da cernelha (AC), comprimento do corpo (CC) e perímetro torácico (PT). Foram observadas correlações signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
2
Order By: Relevance
“…This would be even more important in the pre-weaning phase, when animals are highly efficient in weight gain (Urbano et al, 2017). Mathematical models thus emerge as important tools to describe the growth pattern of ruminant animals Conrado et al, 2015;J. S. Souza et al, 2019), especially when they take into account easily obtained variables, such as age.…”
mentioning
confidence: 99%
“…This would be even more important in the pre-weaning phase, when animals are highly efficient in weight gain (Urbano et al, 2017). Mathematical models thus emerge as important tools to describe the growth pattern of ruminant animals Conrado et al, 2015;J. S. Souza et al, 2019), especially when they take into account easily obtained variables, such as age.…”
mentioning
confidence: 99%
“…It has been used in heifers (Oliveira et al, 2013), and goats and sheep (Conrado et al, 2015;Chay-Canul et al, 2019). Furthermore, several authors have indicated that HG is highly correlated with LW for different animal species (Yilmaz et al, 2013;Chay-Canul et al, 2019a) The authors observed that the quadratic model had the best performance, according to the adequacy assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Animal growth is evaluated using direct measuring equipment, such as livestock scales. However, due to the conditions in which traditional sheep production systems operate (4) , the direct determination of the animals' body weight often represents a challenge for producers because of the high cost of acquiring and maintaining scales (64,65,66,67) . In most cases, this causes producers to market animals based on visual scores, which leads to errors in the estimation of body weight and affects the profitability of production systems (68) .…”
Section: Prediction Of Body Weight and Carcass Traits Of Sheep Throug...mentioning
confidence: 99%